7c-2=2c+23

Simple and best practice solution for 7c-2=2c+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7c-2=2c+23 equation:


Simplifying
7c + -2 = 2c + 23

Reorder the terms:
-2 + 7c = 2c + 23

Reorder the terms:
-2 + 7c = 23 + 2c

Solving
-2 + 7c = 23 + 2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-2c' to each side of the equation.
-2 + 7c + -2c = 23 + 2c + -2c

Combine like terms: 7c + -2c = 5c
-2 + 5c = 23 + 2c + -2c

Combine like terms: 2c + -2c = 0
-2 + 5c = 23 + 0
-2 + 5c = 23

Add '2' to each side of the equation.
-2 + 2 + 5c = 23 + 2

Combine like terms: -2 + 2 = 0
0 + 5c = 23 + 2
5c = 23 + 2

Combine like terms: 23 + 2 = 25
5c = 25

Divide each side by '5'.
c = 5

Simplifying
c = 5

See similar equations:

| 3x^2-2x^3+6=0 | | 15s+9t=27 | | 4sin(2pix)-2=0 | | 4/4x+12 | | -30=4+3(b-6) | | (6x^2+17x+7)/(3x+4) | | 5x+x+4x=180 | | 5x^4/10x^2 | | -145-7x=9x+ | | 4/x+16 | | -2(m-30)=(-6m) | | 2(4n+7)=2n-4 | | (1/4)(x2-y3) | | 5y=9x+5 | | 6m+2=4m+12 | | 2(5y+3)-5=-y-5(4-y) | | 5(2x+2)+10+3x= | | (A*B)-5=5C | | (2x-27)+(x-54)=90 | | 2(x+4)=3x+3 | | 6+5g=21 | | 4(x+2)=2(3x+1) | | 4q*q=2 | | 5x^5+10x^4=0 | | -175+x=-410 | | 137+x=203 | | 456+x=338 | | 103+x=99 | | -498+x=-856 | | (3x/6)+1=7 | | 30w+90=390 | | 94+x=-47 |

Equations solver categories